The effect of using (Posse) strategy in teaching Arabic language on development of reading comperhension skill for Basic 10th grade female students - Mansour, Othman Naser; Mustafa, Shoug Ahmad (Journal of Educational and Psychological Sciences, 2023)
The study aimed at identifying The effectiveness of Using (Predict, Organize, Search, Summarize, Evaluate) (POSSE) Strategy In Teaching Arabic Language on Development of Reading Comprerhension Skills For 10th Grade Female Students. the experimental method with a quasi- experimental design was used. the sample of the study consisted of (80) Female Students who were chosen randomly and divided into two groups. An experimental group consisted of (40) Female Students were taught by the (POSSE) Strategy, and a control group of (40) Female Students were taught by the traditional method, and a test was prepared to measure the reading comprehension skill, consisting of (21) items.The results of the study showed that there were a statistical significant differences between the mean scores of the experimental, and control group in the post-application of the reading comperhension skill on the overall test, at (literal, deductive, critical) levels, in favor of the experimental group of the Female Students, The results of the study also indicated that there were no differences between the mean scores of the experimental and control groups in the post application of the reading comprehension skill test at the creative level. And in the light of the results the study recommended the necesstity of applying the (POSSE) Strategy in teaching Arabic Language for its importance in developing the reading comperhentient skill For Basic 10th Grade Female Students.